2023
DOI: 10.1079/hai.2023.0018
|View full text |Cite
|
Sign up to set email alerts
|

Are children’s relationships with pet dogs uniquely related to children’s social and emotional competence and adjustment?

Abstract: Companion animals, including pet dogs, can be sources of support and potentially contribute to children’s competence and adjustment. The goal of this paper is to examine whether children’s pet dog relationships are related to their competence and adjustment after accounting for relationships with parents and friends and demographic factors. We distinguished three qualities of child-pet dog relationships – positive pet relationship qualities, friction, and pets as substitutes for people – and examined them in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Furthermore, in a study of adult responses from romantic partners to emotional expression, Kane et al (2019) found that interpersonal emotional expression through partner support benefits people that do not typically cope by expressing their feelings; therefore, it could be that pets could play a similar supportive role in a participant's life. This type of compensatory relationship has not been well explored in the context of companion animals, and although recent research did not find initial support for pets compensating for poor peer relationships (Kerns et al, 2023), this is an area that should be explored with longitudinal data.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a study of adult responses from romantic partners to emotional expression, Kane et al (2019) found that interpersonal emotional expression through partner support benefits people that do not typically cope by expressing their feelings; therefore, it could be that pets could play a similar supportive role in a participant's life. This type of compensatory relationship has not been well explored in the context of companion animals, and although recent research did not find initial support for pets compensating for poor peer relationships (Kerns et al, 2023), this is an area that should be explored with longitudinal data.…”
Section: Discussionmentioning
confidence: 99%